People's Perspectives on ID and Civil Registration in Rwanda - World Bank (World Bank, Washington, DC, 2021)
Rwanda's electronic national population register (NPR) and ID project was first launched in 2008 and has since achieved impressive coverage. Today, the NPR captures the information of approximately 98 percent of the population. It is commonly considered to be one of the strongest foundational national identification (ID) systems in Africa due to the robust back end and information management systems that underpin it. The National Identification Agency (NIDA) ), has made concerted efforts over the years in the areas of policy, business process, communications, and support to ensure that all people in Rwanda are able to access IDs and register births and receive birth certificates. This has included initiatives like "CRVS week" in 2017 to encourage people to register the births of their children. It also includes nationwide communications campaigns to ensure equal access to IDs and the ability to use these to access services, with specific targeting for vulnerable groups like refugees. In order to improve current processes, close the remaining two percent gap in ID coverage, and inform the roll out of the new digital birth registration, NIDA requested the World Bank to support qualitative research to understand experiences, attitudes, and behavior of Rwandans towards accessing and using the current national ID cards and birth certificates.